Nearest Neighbor Search on Moving Object Trajectories - Frentzos, Elias; Gratsias, Kostas; Pelekis, Nikos; Theodoridis, Yannis (Advances in Spatial and Temporal Databases, 2005)
With the increasing number of Mobile Location Services (MLS), the need for effective k-NN query processing over historical trajectory data has become the vehicle for data analysis, thus improving existing or even proposing new services. In this paper, we investigate mechanisms to perform NN search on R-tree-like structures storing historical information about moving object trajectories. The proposed branch-and-bound algorithms vary with respect to the type of the query object (stationary or moving point) as well as the type of the query result (continuous or not). We also propose novel metrics to support our search ordering and pruning strategies. Using the implementation of the proposed algorithms on a member of the R-tree family for trajectory data (the TB-tree), we demonstrate their scalability and efficiency through an extensive experimental study using synthetic and real datasets.